PERAN KEPEMIMPINAN DALAM MENUMBUHKAN SOLIDARITAS PEMUDA RANTAU PADA IKPMD-MALANG - Alfiatun, Sumiati Nafisah; Said, M. Mas'ud; Ahmadi, Rulam (Universitas Nahdlatul Ulama Blitar, 2024)
The purpose of this research is to find out how the leadership role of the overseas young generation in IKPMD Malang and to find out the challenges associated with the implementation of leadership in regional organizations. In this study, a qualitative descriptive research method was applied. Methods such as in-depth interviews and observation were used to conduct qualitative research. The researcher conducted a thorough analysis of the field data using this strategy. To find out the role of leadership in fostering the solidarity of overseas youth and the challenges faced by youth in the organization, researchers used descriptive qualitative methods and interviewed the Chairperson of IKPMD Malang, IKPMD Malang administrators, and one of the active members of IKPMD Malang. The findings of this study discuss the function of youth leadership in fostering communities abroad. Specifically, the leadership designs work programs which include athletics, IKPMD greetings, social work programs (intimacy nights), religious studies and talks, and major work programs. Budget, low member involvement, and the challenge of bringing all IKPMD-Malang members together are the challenges.